A study on the relationship between morale of employees and project performance in the consrtuction industry in Kedah - Fadhilah, Ahmad (2014)
This thesis was conducted to determine the relationship between morale of employees and project performance in the construction industry. Based on a study conducted by the American Management Association study reported that among firms applying job cuts in the 1990s, 69 percent reported a decline in employee morale. This shows that morale of employees is one of important factor in the companies and organization; they should focus more on this factor to ensure best in project performance. The literature review is about the information for each variable that are used in this study, which are job satisfaction, Esprit de Corps and motivation as an independent variable. For dependent variable it would explain the information about time performance and quality performance. Besides that, this study using Krejcie & Morgan (1970) table to calculate the sample size and 44 contractors’ from Grade 4 (G4) in Kota Setar, Kedah had been chosen as respondent of this study. In methodology, this research used quantitative method and questionnaire as a main instrument to collect the data. These questionnaires consist of three sections which are section A: Demographic, section B: Morale of employees and section C: Project performance. The data that are collected from the questionnaire will be analyzed by using Statistical Package for the Social Science (SPPS) database software. Descriptive analysis, reliability analysis, ranking analysis, Pearson correlation analysis, regression analysis and analysis of hypothesis were used in the data analysis. Ranking analysis show that motivation is the higher rankings that lead to project performance and follow by job satisfaction and Esprit de Corps. From the data obtained from multiple regression analysis, all hypotheses are accepted. In conclusion, there is a positive relationship between morale of employees and project performance